Merozoite surface protein 2 allelic variation influences the specific antibody response during acute malaria in individuals from a Brazilian endemic area - Selma Sallenave-Sales; Clarissa Perez Faria; Mariano Gustavo Zalis; Cláudio Tadeu Daniel-Ribeiro; Maria de Fátima Ferreira-da-Cruz (Memorias do Instituto Oswaldo Cruz, 2007)
The antibody response to Plasmodium falciparum parasites of naturally infected population is critical to elucidate the role of polymorphic alleles in malaria. Thus, we evaluated the impact of antigenic diversity of repetitive and family dimorphic domains of the merozoite surface protein 2 (MSP-2) on immune response of 96 individuals living in Peixoto de Azevedo (MT-Brazil), by ELISA using recombinant MSP-2 proteins. The majority of these individuals were carrying FC27-type infections. IgG antibody responses were predominantly directed to FC27 parasites and were correlated to the extension of polymorphism presented by each MSP-2 region. This finding demonstrated the impact of the genetic polymorphism on antibody response and therefore, its importance on malaria vaccine efficacy.